Studi Deskriptif Nilai Karakter Projek Penguatan Profil Pelajar Pancasila (P5) Dalam Cerita Rakyat Bengkulu Selatan - Illahi, Fauzi Taufiq; Muktadir, Abdul; Kurniawati, Ike (Universitas Bengkulu, 2025)
This study aims to describe the character values of P5 in the folklore of Sang Piatu, Batu Amparan Gading, and Si Kancil Jahil. This type of research is Qualitative with a descriptive method. The subjects in this study were 3 folklores of South Bengkulu, namely Sang Piatu, Batu Amparan Gading, and Si Kancil Jahil. The research instrument was the researcher himself using a table of character values and using a descriptor table of each character value. The data analysis technique used the content analysis technique. The data validity technique was through diligent observation and auditing. Based on the results of the study on the character values of P5 in the folklore book of South Bengkulu, it was found that each story contained 5 character values out of 6 character values studied. The character values that often appear in the three folklores studied are 1) Faith, devotion to God Almighty, and noble character, 2) Mutual cooperation, 3) independence, and 4) critical thinking. The Creative character value only appears in two folktales, namely the Batu Amparan Gading and Si Kancil Jahil folktales. Meanwhile, the global diversity character value only appears in the Sang Piatu folktale. The character value is obtained from the dialogue and narrative quotes from the characters in the folktale.